2019
DOI: 10.1111/1440-1681.13165
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic characterisation of the optimised rat model of Walker 256 breast cancer cell‐induced bone pain

Abstract: In patients with breast cancer, metastases of cancer cells to the axial skeleton may cause excruciating pain, particularly in the advanced stages. The current drug treatments available to alleviate this debilitating pain condition often lack efficacy and/or produce undesirable side effects. Preclinical animal models of cancer‐induced bone pain are key to studying the mechanisms that cause this pain and for the success of drug discovery programs. In a previous study conducted in our laboratory, we validated and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 94 publications
(94 reference statements)
0
2
0
Order By: Relevance
“…The BCP model was established according to the method previously reported ( Zhou et al, 2015 ; Hu et al, 2019 ; Shenoy et al, 2019 ; Zhang et al, 2020 ). In detail, the young rat was intraperitoneally injected with 2 × 10 7 Walker 256 cells.…”
Section: Methodsmentioning
confidence: 99%
“…The BCP model was established according to the method previously reported ( Zhou et al, 2015 ; Hu et al, 2019 ; Shenoy et al, 2019 ; Zhang et al, 2020 ). In detail, the young rat was intraperitoneally injected with 2 × 10 7 Walker 256 cells.…”
Section: Methodsmentioning
confidence: 99%
“…For the purpose, dozens of models of BCP have been successfully established in rats and mice over the past decades. 4 A growing number of findings obtained in these models have revealed that some critical genes, 5 RNAs, [6][7][8] peptides/protein (e.g., calcitonin gene-related peptide, neuropeptide Y, PI3K/Akt) [9][10][11] and small biochemical molecules (e.g., D-serine, glycine) 12,13 in the spinal cord were complicatedly involved in BCP through a variety of mechanisms, including central sensitization, oxidative stress, neuroinflammation, glial cell activation, mitochondrial dysfunction and others. 11,[14][15][16][17] However, BCP is still a major clinical challenge due to its potential unclear pathologic mechanisms.…”
Section: Introductionmentioning
confidence: 99%